Interleukin-12p35 Deficiency Reverses the Th1/Th2 Imbalance, Aggravates the Th17/Treg Imbalance, and Ameliorates Atherosclerosis in ApoE-/- Mice. (10th April 2019) - Huang, Ying; Hu, Haiying; Liu, Ling; Ye, Jing; Wang, Zhen; Que, Bin; Liu, Wenjing; Shi, Ying; Zeng, Tao; Shi, Lei; Ji, Qingwei; Chang, Chao; et al.
Abstract : Interleukin- (IL-) 35, a novel functional cytokine of regulatory T cells (Treg) comprised of the IL-12p35 subunit and the other subunit Epstein-Barr virus-induced gene 3 (EBI3), regulates the activity of CD4+ T cells and macrophages, thereby playing a critical role in inflammatory and autoimmune diseases. Previous studies demonstrated that both recombinant mice and human IL-35 attenuated atherosclerosis in ApoE-/- mice. Additionally, EBI3 deficiency enhanced the activation of macrophages and increased atherosclerotic lesions in LDLR-/- mice. This study generated double-deficient mice for ApoE and IL-12p35 (ApoE-/- IL-12p35-/- mice) and investigated the effect of IL-12p35 deficiency on atherosclerosis. IL-12p35 deficiency alleviated Th1/Th2 imbalance, aggravated Th17/Treg imbalance, and attenuated atherosclerotic plaque formation in ApoE-/- mice. Additionally, exogenous rIL-35 treatment reversed the imbalance of Th17/Treg and attenuated atherosclerosis in ApoE-/- mice. These findings suggest that IL-12p35 deficiency ameliorates atherosclerosis in ApoE-/- mice, partially, via attenuating the Th1/Th2 imbalance, although IL-12p35 deficiency aggravates the Th17/Treg imbalance.